Little Hand's Board Book Opposite & Action Words - Zain,Shama (PARAMOUNT BOOKS (PVT) LTD.)
Little Hand$1 (Bs Board Books are your toddler$1 (Bs best companion that will stand by them despite the tugs and pushes of the little hands. These books will ignite their wonder to learn new things at the developmental stage with the delightful and vibrant illustrations. These hard board books will cement their learning at the foundation level of reading, writing and speaking, where they will associate words with pictures and recognise unfamiliar objects while developing their cognitive and language abilities. One of the best things at early childhood education level to develop a habit of reading and learning.s
Keywords: English board book